SIFAT ORGANOLEPTIK DAN NILAI GIZI PUDING U-BANSOY (ULI BANANA SOYA) SEBAGAI ALTERNATIF SELINGAN TINGGI KALIUM DAN ISOFLAVON UNTUK PENDERITA HIPERTENSI - Nurhotimah, Enung; Aeni, Muna Nur; Gumilar, Mulus; Fitria, Mona; Judiono, Judiono; Mulyo, Gurid Pramintarto Eko (Poltekkes Kemenkes Bandung, 2023)
Uli bananas contain higher potassium than other types of bananas. Soybeans can help lower blood pressure in hypertensive patients through potassium content and antioxidant activity, as shown by isoflavones. This study aimed to determine the organoleptic properties and nutritional value of U-Bansoy Pudding with soybean and banana formulations as an alternative high-potassium and isoflavone snacks for hypertensive patients. The research design used an experimental study design using a Complete Experimental Design (RAL) consisting of one factor in the form of 3 types of soybean and banana balance, namely 25%:75%, 50%:50%, 75%:25%. The research method used an organoleptic test with a hedonic test of 7 numerical scale on 30 moderately trained panelists. The results of U-Bansoy Pudding organoleptic test on the color and texture that the panelists liked the most was a 50%:50% balance. U-Bansoy pudding organoleptic test results on the aroma that the panelists most liked were the balance of 25%:75% and 50%:50%, while the results of the organoleptic test of U-Bansoy pudding on the taste and overall (overall) balance of 25%:75% were the most preferred by the panelists. By consuming one serving of U-Bansoy Pudding with a balance of 25%:75% is enough to contribute as an alternative distraction for hypertensive patients with 185.95 grams of energy, 8.74 grams of protein, 3.64 grams of fat, 34.2 grams of carbohydrates, 533.14 mg of potassium and 30.9 mg of isoflavones. U-Bansoy pudding can be used as an alternative snack for hypertensive patients who need a diet high in potassium and isoflavones.